Phonetic and phonological aspects of Civili vowel duration : an experimental approach - Ndinga-Koumba-Binza, Hugues Steve (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DLitt (African Languages))--University of Stellenbosch, 2008.